A CRITICAL DISCOURSE ANALYSIS OF NEWS ARTICLES ON THE DISPUTED QUICK COUNT RESULTS DURING THE 2014 INDONESIAN PRESIDENTIAL ELECTION - Anwar, Muhammad Syaeful (2015)
During the 2014 Indonesian presidential election, the issue of different quick count results became a heated debate among Indonesians. In fact, the issue had divided the country into two opposing camps, the Prabowo and Jokowi camps. This research paper is aimed at exposing how a single reality, the issue of different quick count results, is represented and viewed in two news websites,Okezone and Tempo. Further, it also attempts to investigate the role of the news websites in shaping public opinions and attitudes towards the issue. To achieve these aims, van Dijk's (2009) sociocognitive approach to Critical Discourse Analysis (CDA) is used to analyze two news articles from each side. Relying on the analyses of context, macrostructures, local meanings, and formal structures, the studyshows that Okezone seems to identify itself as a member of the Prabowo camp and judge the actions of the Jokowi camp negatively. On the contrary, Tempo seems to classify itself as a member of the Jokowi camp and evaluates the actions of the Prabowo camp negatively and those of the Jokowi camp positively. The general strategy used by Okezone to manipulate the readers' opinions and views towards the issue is negative-other presentation, emphasizing the bad properties of the Jokowi camp. Meanwhile, Tempo employs a combined strategy of negative-other presentation, emphasizing the bad properties of the Prabowo camp, and positive-self presentation, emphasizing the good properties of Jokowi's camp. Keywords: Quick count, Prabowo, Jokowi, Okezone, Tempo, critical discourse analysis, sociocognitive approach, underlying ideologies Selamapemilihanumumpresiden 2014, isuperbedaanhasilhitungcepatmenjadiperdebatanpanas di Indonesia. Bahkan, isutersebuttelahmembagirakyat Indonesia kedalamduakubu yang berlawanan, yaknikubuPrabowodankubuJokowi. Skripsiinibertujuanuntukmenyingkapbagaimanarealitas yang sama, isuperbedaanhasilhitungcepat, direpresentasikandandilihatdalamduasitusberita, Okezonedan Tempo. Skripsiini pun bertujuanuntukmengusutperankeduasitusberitatersebutdalammembentukopinidansikappublikterhadapisutersebut. Untukitu, pendekatansosiokognitif van Dijk (2009) terhadapCritical Discourse Analysis (CDA) digunakanuntukmenganalisaduaartikelberitadaritiap situs. Berdasarkanhasilanalisiscontext, macrostructures, local meanings, danformal structuresditemukanbahwaOkezonememihakkepadakubuPrabowodanmenilaitindakan yang dilakukanolehkubuJokowisecara negative. Sebaliknya, Tempo memihakpadakubuJokowidanmenilaitindakan yang dilakukanolehkubuPrabowosecaranegatifdantindakankubuJokowisecarapositif. Strategiumum yang digunakanolehOkezoneuntukmemanipulasipendapatdanpandanganpembacaterhadapisuperbedaanhasilhitungcepatadalahnegative-other presentation, menonjolkankeburukandarikubu Jokowi. Sementaraitu, Tempo menggunakanstrategigabungannegative-other presentation, menonjolkankeburukankubuPrabowo, danpositive-self presentation, menonjolkankebaikankubuJokowi. Kata kunci: Quick count, Prabowo, Jokowi, Okezone, Tempo, critical discourse analysis, sociocognitive approach, underlying ideologies